2022
DOI: 10.1177/14738716221086589
|View full text |Cite
|
Sign up to set email alerts
|

Visual cluster separation using high-dimensional sharpened dimensionality reduction

Abstract: Applying dimensionality reduction (DR) to large, high-dimensional data sets can be challenging when distinguishing the underlying high-dimensional data clusters in a 2D projection for exploratory analysis. We address this problem by first sharpening the clusters in the original high-dimensional data prior to the DR step using Local Gradient Clustering (LGC). We then project the sharpened data from the high-dimensional space to 2D by a user-selected DR method. The sharpening step aids this method to preserve cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(50 citation statements)
references
References 80 publications
0
50
0
Order By: Relevance
“…In a related vein, (Rodrigues et al, 2019) used the VS in projections to construct so-called decision boundary maps to interpret classification performance (CP) but did not actually use these to improve classifiers. (Kim et al, 2022b;Kim et al, 2022a) showed that one can improve VS by increasing DS, the latter being done by mean shift (Comaniciu and Meer, 2002). However, their aim was to generate easier-to-interpret projections and not use these to build higher-CP classifiers.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In a related vein, (Rodrigues et al, 2019) used the VS in projections to construct so-called decision boundary maps to interpret classification performance (CP) but did not actually use these to improve classifiers. (Kim et al, 2022b;Kim et al, 2022a) showed that one can improve VS by increasing DS, the latter being done by mean shift (Comaniciu and Meer, 2002). However, their aim was to generate easier-to-interpret projections and not use these to build higher-CP classifiers.…”
Section: Related Workmentioning
confidence: 99%
“…Two key observations were made in this respect (discussed in detail in Sec. 2): O1 Visual separability (VS) in a projection mimics the data separability (DS) in the high dimensional space; O2 Data separability (DS) is key to achieving high classifier performance (CP); These observations have been used in several directions, e.g., using projections to assess DS (VS→DS) (der Maaten et al, 2009); using projections to find which samples get misclassified arXiv:2302.02663v1 [cs.LG] 6 Feb 2023 (VS→CP) (Nonato and Aupetit, 2018); increasing DS to get easier-to-interpret projections (DS→VS) (Kim et al, 2022b); using projections to assess classification difficulty (VS→CP) (Rauber et al, 2017a;Rauber et al, 2017b); and using projections to build better classifiers (VS→CP) (Benato et al, 2018;Benato et al, 2021a). However, to our knowledge, no work so far has explored the relationship between DS, VS, and CP in the context of using pseudo-labeling for machine learning (ML).…”
Section: Introductionmentioning
confidence: 99%
“…Other computational/algorithmic improvements have enabled significant speed-ups for UMAP compared to t-SNE although in essence, the algorithms share significant similarities and the t-SNE implementation from Poličar et al (2019) is competitive with UMAP in terms of computational time. Despite its relatively recent creation, the UMAP algorithm has already found use in astrophysics applications (Reis et al 2019;Kim et al 2022;Grondin et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Information Visualization, 21(3):197-219, 2022. [112] • Chapter 3: J. Heo * , Y. Kim * , and J. B. T. M. Roerdink.…”
Section: S a M E N Vat T I N Gmentioning
confidence: 99%
“…We have also evaluated other nearest-neighbor search algorithms (see Section 2.6.1). Our code is publicly available [110].…”
Section: Number Of Iterations 𝑡mentioning
confidence: 99%